‘The place where you should have been born’—Conservation practitioners sacralising wilderness and developing a sense of belonging in the Manu National Park, Perú - Eduardo Salazar Moreira (People and Nature)
Abstract The management of protected areas is often portrayed as an enterprise guided by objective knowledge and technical criteria, a claim that situates conservation practitioners in positions of power relative to other actors in these spaces. Challenging these claims of objectivity by exploring conservation practitioners' subjective views is vital to facilitate more equitable conservation management. Through a critical analysis of online interviews with conservation practitioners, archival material and participants' photographs, and of my experience as a conservation practitioner, I explore how detrimental elements of wilderness ideology continue to affect these experts' subjectivities. My analysis is grounded in the case of the Manu National Park in the Peruvian Amazon, a conservation space regarded as legendary and mythical by biodiversity enthusiasts despite its problematic relations with Indigenous communities. I show that conservation practitioners' subjectivities can reproduce shared notions of sacredness and belonging that discursively appropriate spaces and contribute to the discursive and material displacement of Indigenous peoples. Exceptions to this pattern reveal that conservation practitioners can develop inclusive emotional and relational connections with conservation spaces and with the Indigenous communities that inhabit them. This, however, is the result of practitioners having meaningful long‐term interactions with local Indigenous communities in Indigenous spaces, instead of interacting mostly with other conservation practitioners. Synthesis and applications. Considering these results, the processes of reflexivity that conservation practitioners need to engage with to drive transformational change in conservation practice could be facilitated by collective experiences outside of social environments where conservation principles are dominant. Read the free Plain Language Summary for this article on the Journal blog.